Multicentre, non-interventional study of the efficacy and tolerability of linaclotide in the treatment of irritable bowel syndrome with constipation in primary, secondary and tertiary centres: the Alpine study. Issue 12 (30th December 2019) - Pohl, Daniel; Fried, Michael; Lawrance, Dominic; Beck, Elmar; Hammer, Heinz F.
Abstract : Objectives: We evaluated the effectiveness and tolerability of linaclotide, a minimally absorbed guanylate cyclase-C agonist, in patients with irritable bowel syndrome with constipation (IBS-C) in routine clinical practice. Setting: A multicentre, non-interventional study conducted between December 2013 and November 2015 across 31 primary, secondary and tertiary centres in Austria and Switzerland. Participants: The study enrolled 138 patients aged ≥18 years with moderate-to-severe IBS-C. Treatment decision was at the physician's discretion. Patients with known hypersensitivity to the study drug or suspected mechanical obstruction were excluded. The mean age of participants was 50 years, and >75% of the patients were women. 128 patients completed the study. Primary and secondary outcome measures: Data were collected at weeks 0 and 4 in Austria and weeks 0, 4 and 16 in Switzerland. The primary effectiveness endpoints included severity of abdominal pain and bloating (11-point numerical rating scale [0=no pain/bloating to 10=worst possible pain/bloating]), frequency of bowel movements and physicians' global effectiveness of linaclotide. Treatment-related adverse events (AEs) were recorded. Results: Following a 4-week treatment period, the mean intensity score of abdominal pain was reduced from 5.8 at baseline to 2.7, while the bloating intensity score was reduced from 5.8 at baseline to 3.1e (both indices p<0.001). The frequency of mean weekly bowel movements increased from 2.1 at baseline to 4.5 at week 4 (p<0.001). Global effectiveness and tolerability of linaclotide were assessed by the treating physicians as 'good' or 'excellent' in >70% of patients. In total, 31 AEs were reported in 22 patients, the most common being diarrhoea, reported by 6 (7%) and 8 (15.4%) patients in Austria and Switzerland, respectively. Conclusions: Patients with IBS-C receiving linaclotide experienced effective treatment of moderate-to-severe symptoms in routine clinical practice. Linaclotide was safe and well tolerated and no new safety concerns were raised, supporting results from previous clinical trials.